Jawabanmu

2014-04-17T19:21:16+07:00
A.)
f(x) = 4 - 8x
f'(x) => 4-8x = x'
           4-x' = 8x
             x = 4-x'
                    8
g(x) = 20x -7
         25x -2
g'(x) => 20x - 7 = x'
            25x - 2
            20x-7 = x' (25x-2)
            20x-7 = 25xx' - 2x'
            -7 + 2x' = x (25x' - 20)
                     x =    2x' - 7
                           25x' - 20

B.) gof (x) => masukkan nilai f(x) ke dalam g(x)
     20x - 7 =>  20(4-8x) - 7  => 80 -160 x-7    => 73 - 160x
     25x - 2       25(4-8x) -2       100 - 200x -2       98 - 200x
     fog(x) => masukkan nilai g(x) ke dalam f(x)

C.) sama masukkan g'(x) ke dalam f'(x) dan f'(x) ke dalam fungsi g'(x)